Dicionário-aberto: a source of resources for the portuguese language processing - Simões, Alberto (2012)
In this paper we describe how Dicionáio-Aberto, an online dictionary for the Portuguese language, is being used as the base to construct diverse resources that are relevant in the processing of the Portuguese language. We will briefly present its history, explaining how we got here. Then, we will describe the resources already available to download and use, followed by the discussion on the resources that are being currently developed.